Prognostic Factors of Renal Outcomes after Heart Transplantation: A Nationwide Retrospective Study - Junseok Jeon (MDPI AG, 2021)
Renal dysfunction after heart transplantation (HT) is associated with poor survival. We investigated the predictive factors of renal outcomes after HT using nationwide cohort data. In this retrospective cohort study using the Health Insurance Review and Assessment database of Korea, 654 patients who received HT between 2008 and 2016 and survived until discharge after HT were analyzed. The median (interquartile range) age was 52 (40–60) years, and 68.1% were male. Perioperative renal replacement therapy (RRT) was performed in 27.8% of patients. During 2.8 years of median followup, end-stage kidney disease (ESKD) developed in 12 patients (1.8%). In a fully adjusted model, RRT > 3 weeks, the use of inotropes/vasopressors and non-use of ACEi/ARB were associated with ESKD. Preexisting renal disease tended to be associated with ESKD. Among the 561 patients without preexisting CKD, 104 (18.5%) developed chronic kidney disease (CKD). Age, extracorporeal membrane oxygenation, and RRT were associated with the development of CKD after HT. Our nationwide cohort study demonstrated that perioperative RRT was a predictor of poor renal outcomes after HT. These results suggest that an active renoprotective strategy is required during the perioperative period.